Наратив родинного Святого вечора в дитячих спогадах переселенців із Західної Бойківщини: антропологія пам’яті - Коломийчук, О. (Народна творчість та етнологія, 2021)
У статті проаналізовано наративи українців, примусово переселених із території Західної Бойківщини в рамках операції «Вісла» в 1947 році, які стосуються родинних традицій у відзначенні Святого вечора в рідних для них місцевостях. Дослідженнями було охоплено північні та північно-західні воєводства сучасної Республіки Польща, де й осіли українці-переселенці Західної Бойківщини, а саме: Західнопоморське (м. Білий Бір, сс. Каліска, Димінек (Щецинецький повіт), м. Кошалін (Кошалінський повіт)) та Вармінсько-Мазурське (м. Ґурово-Ілавецьке, м. Пенєнжно (Браневський повіт), с. Шимбори (ґміна Ґодково, Ельблонґський повіт)) воєводства. Усі інформатори – жінки, що народилися між 1925 та 1937 роками. Їхні наративи стосуються часу, коли респонденти були переважно дітьми, рідше – підлітками, тому інформацію про обрядові традиції Святого вечора у своїх родинах черпають передусім із дитячих спогадів. Варто додати, що на сучасному етапі безпосередні свідки примусового переселення досить дисперсно проживають у польському етнокультурному середовищі, по суті, не створюючи окремих спільнот пам’яті вихідців із субрегіону Західної Бойківщини. На основі методологічної перспективи, що розглядає пам’ять як інструмент пізнання (К. Каньовська), у статті досліджуються структура та семантичні особливості тексту наративів, встановлюється взаємозв’язок змісту спогадів із механізмом їх пригадування. Аналізовані фрагменти текстів із наративів переміщених осіб дають уявлення про способи та механізми реконструкції родинних обрядових традицій на Святвечір у пам’яті їхніх авторів. Установлено, що такі звичаєво-обрядові дії, як розстеляння соломи на долівці, пошук у ній горіхів, обрядове годування худоби, спільне внесення обрядових атрибутів до хати, ритуал-діалог чоловічої частини родини з жіночою, фактично маркують святково-обрядовий простір Святого вечора в пам’яті дитинства переселенців, яка водночас є частиною так званої колективної пам’яті родини. При цьому одним зі стрижнів процесу пригадування в дорослому віці є, власне, родинна традиція, що в умовах чужого мовно-культурного середовища є певним каталізатором збереження власного етнічного «я». Однак в умовах достатньої розпорошеності переселенців із Західної Бойківщини на рівні родин, високого ступеня однорідності польського етнокультурного середовища, а також у зв’язку з відходом старшого покоління (батьків оповідачів), яке виступало, так би мовити, «ретранслятором» автентичної обрядової культури, процес міжпоколінної трансмісії порушений. Загалом, як переконують наративи наших оповідачів, багаті родинні традиції у відзначенні Святого вечора залишаються лише певним «спогадом у мені» безпосередніх свідків операції «Вісла» й фактично мало впливають на формування звичаєво-обрядової картини світу наступних поколінь переселенців. The article analyzes the narratives of the Ukrainians forced to resettle from the territory of Western Boykivshchyna during Operation Vistula in 1947, which are related to the familial traditions of Christmas Eve observance in their homeland. Territories covered by the study are northern and northwestern voivodeships of the Republic of Poland, where displaced Ukrainians have resettled, namely: West Pomeranian Voivodeship [town of Biały Bór, villages Kaliska and Dyminek (Szczecinek County), city of Koszalin (Koszalin County)] and Warmian-Masurian Voivodeship [towns Górowo Iławeckie (Bartoszyce County) and Pieniężno (Braniewo County), and the village of Szymbory (Gmina Godkowo, within Elbląg County)]. All informants are women born between 1925 and 1937. The narratives under consideration are related to the time when the interviewed respondents were mostly children, less often teenagers; consequently, they draw information about the ritual traditions of Christmas Eve observed in their families primarily from their childhood recollections. It should be added that currently, direct witnesses of forced displacement live quite dispersedly in the Polish ethno-cultural environment, in fact, without creating separate communities of memorializing the people who originated from the sub-region of Western Boykivshchyna. Based on the methodological perspective, which considers memory as an instrument of cognition (Katarzyna Kaniowska), the article analyzes the structure and semantic features of a text of narratives, as well as determines an interconnection between the content of memories and the mechanism of their recollection. The analyzed fragments of texts from the narratives of displaced persons give an opportunity to comprehend the ways and mechanisms of reconstructing the familial ritual traditions of Christmas Eve observance in the memory of their authors. It is established that such customary-ritual actions as spreading straw on the earthen floor, searching for nuts in it, ritual feeding of cattle, common introduction of ritual attributes into the house, and a ritual-dialogue of a family’s male part with the female one actually mark the festive-ceremonial space of Christmas Eve in the memory of immigrants’ childhood, which is simultaneously a part of the so-called collective memory of a family. At the same time, one of the cores of the remembrance process in adulthood is, in fact, a family tradition, which, in the conditions of an alien linguistic and cultural environment, acts as a catalyst for preserving one’s own ethnic self. However, the process of intergenerational transmission is disrupted due to the factors of the considerable dispersion of immigrants from Western Boykivshchyna at the familial level, a high degree of homogeneity of the Polish ethno-cultural environment, as well as owing to the departure of the older generation (parents of narrators), which acted as a retransmitter of an authentic ritual culture. In general, as we can see from the narratives of our storytellers, the rich familial traditions in celebrating Christmas Eve remain only a certain memory in myself / keeping memory to myself of the direct witnesses of Operation Vistula and actually have little effect on forming a customary-ritual picture of the world of much younger generations of displaced persons.